The financial aspect of parliamentary private bill procedure - Stanuell, Charles A. (Statistical and Social Inquiry Society of Ireland, 1906)
The mode of conducting Parliamentary Inquiries into Private Bills relating to this country has been the subject of criticism for many years, and it has been brought before the public on many occasions, while it has frequently been made the subject of papers read before this Society. This renders it unnecessary to go at any great length into an explanation of the existing system, but still I think it is well to refer briefly to the present procedure so that the subsequent criticism may be clear and definite.
Read Tuesday 15th January, 1901
Keywords: Private bill legislation; Financial cost; 314.15